ANALISIS STRATEGI PEMBERDAYAAN MASYARAKAT PETANI DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI RUMAH TANGGA (Studi Kasus di Desa Jarangan, Kec.Rejoso, Kab. Pasuruan) - Robilaong, Aldy; Brillian Pintakami, Lintar; Dewi Oryza Sativa, Rima (Universitas Islam Balitar, 2022)
This study aims to 1) Describe empowerment programs for farming communities in the Tourism Village area. 2) Analyze the factors influencing farming communities to be empowered. 3) Identify the involvement of farming communities and their level of well-being. 4) Analyze the development strategy of Tourism Village. The results showed that the empowerment program has been carried out, namely in the form of Regular Meetings of agro-tourism plans, technical guidance, introduction of local products, counseling, and also the construction of agro-tourism facilities. An influential factor in the existence of empowerment is because Jarangan Village has natural resources that have the potential to be in mangrove forests and also natural wealth in the form of processed marine products. Community involvement for agro-tourism empowerment and management programs is fairly even and the level of community welfare is also gradually increasing. Rare Mangrove Tourism Village is still relatively developed so it requires empowerment based on a SWOT analysis.